2021
DOI: 10.3390/fluids6030102
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-Structure Interaction of Flexible Whisker-Type Beams and Its Implications for Flow Sensing by Pair-Wise Correlation

Abstract: (1) Background: Sensing of critical events or flow signatures in nature often presents itself as a coupled interaction between a fluid and arrays of slender flexible beams, such a wind-hairs or whiskers. It is hypothesized that important information is gained in highly noisy environments by the inter-correlation within the array. (2) Methods: The present study uses a model sea lion head with artificial whiskers in the form of slender beams (optical fibres), which are subjected to a mean flow with overlaid turb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…We have shown via a physical demonstration, that an array of whiskers can be used as a reliable system of sensors for determining the DoA, via noise resistant GCC algorithms 12,17 , multilateration of triplets of whiskers, and using methods adapted from audio and other source localisation techniques. The relevance of this study is related to the previously reported sensing capabilities of sea lions exposed to a traveling vortex ring, passing one of the vibrissal pads on their heads 10 .…”
Section: Discussionmentioning
confidence: 99%
“…We have shown via a physical demonstration, that an array of whiskers can be used as a reliable system of sensors for determining the DoA, via noise resistant GCC algorithms 12,17 , multilateration of triplets of whiskers, and using methods adapted from audio and other source localisation techniques. The relevance of this study is related to the previously reported sensing capabilities of sea lions exposed to a traveling vortex ring, passing one of the vibrissal pads on their heads 10 .…”
Section: Discussionmentioning
confidence: 99%
“…We have shown via a physical demonstration, that an array of whiskers can be used as a reliable system of sensors for determining the DoA, via noise resistant GCC algorithms 12 , 18 , multilateration of triplets of whiskers, and using data processing methods adapted from audio and other source localisation techniques. The relevance of this study is related to the previously reported sensing capabilities of sea lions exposed to a traveling vortex ring, passing one of the vibrissal pads on their heads 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to further research the influence of temporal coding within the array on the response. Interesting in that context is the recent study 12 with pairs of artificial whisker proving that a pair-wise cross-correlation of whiskers can decode the convection velocity. These time delays can be further used to triangulate the position of the source, using techniques adapted from radio localisation.…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of past studies focused on the mechanism of single whisker sensing, little has been studied on the flow sensing at the whisker array level. During the process of sensing, seals extract flow information based on the interaction between their whisker arrays and the surrounding fluids [17,18]. With the presence of flow disturbance, each whisker can be dynamically bent in response to its hydrodynamic loading [18].…”
Section: Introductionmentioning
confidence: 99%
“…During the process of sensing, seals extract flow information based on the interaction between their whisker arrays and the surrounding fluids [17,18]. With the presence of flow disturbance, each whisker can be dynamically bent in response to its hydrodynamic loading [18]. The resulting reaction force and bending moments at the vibrissal base constitute the primary mechanical inputs to neural circuits and form the basis for vibrissotactile perception [19].…”
Section: Introductionmentioning
confidence: 99%